Synthesis, physical and chemical properties of 2-((4-R-3-(morfolinomethylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts - R. О. Shcherbyna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Today’s medicine and pharmacy undoubtedly need new and effective drugs. The 1,2,4-triazole derivatives occupy a special place among the wide variety of active organic compounds. This interest is caused primarily by high biological activity of these derivatives, low toxicity and high accessibility in terms of synthesis. Thus, drugs from 1,2,4-triazoles are known and are used extensively in medicine. It is important that a sufficiently large number of scientists-synthetics are paying attention on the heterocyclic system. Although a huge amount of information in the scientific literature is devoted to the 1,2,4-triazole derivatives, the 2-((4-R-3-(morfolinometylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts are virtually unexplored.